2002
DOI: 10.1097/00003226-200211000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Corneal Erosions Using Autologous Serum

Abstract: The use of autologous serum for the treatment of patients with recurrent corneal erosion is effective and safe in reducing the number of recurrences experienced by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 20 publications
1
62
1
2
Order By: Relevance
“…49 The treatment is safe with no secondary effects. 50 However, further studies are needed on larger series and with longer follow-up to determine the ideal duration of treatment and the mechanism of action.…”
Section: Autologous Serummentioning
confidence: 99%
“…49 The treatment is safe with no secondary effects. 50 However, further studies are needed on larger series and with longer follow-up to determine the ideal duration of treatment and the mechanism of action.…”
Section: Autologous Serummentioning
confidence: 99%
“…Therefore, it may be used for the treatment of ocular surface diseases including persistent corneal epithelial defect. 8 It has been reported that the concentration of EGF is higher in tears, while that of vitamin A and TGF-β is higher in the serum. 25 Similarly, a higher concentration of substance P, NGF, and IGF-1 has been detected in the serum.…”
mentioning
confidence: 99%
“…1,[3][4][5][6][7][8] However, in regard to autologous serum, its shortcomings are that it requires repeated blood collection from patients, and that it is sometimes accompanied by discomfort or by treatment refusal by some patients. Also, it is difficult to obtain blood from patients with poor general condition or blood dyscrasia.…”
mentioning
confidence: 99%
“…Del Castillo et al (23) studied the effect of 20% autologous serum in the treatment of recurrent corneal erosions in 11 eyes of 11 patients. Mean follow-up time was 9.4 ± 3.7 months (range, 4 to 16).…”
Section: Recurrent Corneal Erosionmentioning
confidence: 99%